2007
DOI: 10.1017/s175173110768505x
|View full text |Cite
|
Sign up to set email alerts
|

Post-ruminal or intravenous infusions of carbohydrates or amino acids to dairy cows 1. Early lactation

Abstract: The objectives of this study were to compare the effects of post-ruminal and intravenous infusions of wheat starch or glucose (CHO) or a mixture of amino acids (AA) on milk protein yield, nitrogen utilisation, plasma metabolites and mammary extraction rate of dairy cows in early lactation. Eight cow, ruminally fistulated, was assigned to two 4 £ 4 Latin squares during 14-day periods, where the last 7 days were for infusions. Infusions were: (1) starch in the abomasum (SP), (2) glucose in the blood (GB), (3) AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…However, the increased activity of membrane transporters may not be cell specific, and thus competition between organs may be detrimental for the intracellular AA supply of mammary epithelial cells. By improving the extraction rate, Schei et al (2007a) also observed a higher extraction rate of essential AA during intravenous infusion of a mixture of AA, but the effects were larger after glucose infusion. These effects were observed in early lactation, but were inconsistent in late lactation (Schei et al, 2007b).…”
Section: Factors Affecting the Efficiency Of N Utilization In The Mammentioning
confidence: 90%
“…However, the increased activity of membrane transporters may not be cell specific, and thus competition between organs may be detrimental for the intracellular AA supply of mammary epithelial cells. By improving the extraction rate, Schei et al (2007a) also observed a higher extraction rate of essential AA during intravenous infusion of a mixture of AA, but the effects were larger after glucose infusion. These effects were observed in early lactation, but were inconsistent in late lactation (Schei et al, 2007b).…”
Section: Factors Affecting the Efficiency Of N Utilization In The Mammentioning
confidence: 90%
“…The cows were the same as used in the early lactation experiment presented in our accompanying paper (Schei et al, 2007). The experiment was conducted in late lactation starting 165^4 (mean^s.e.)…”
Section: Methodsmentioning
confidence: 99%
“…days post partum (milk yield 22.5^1.1 kg). The cows were fed the same basal ration consisting of concentrate and grass silage in the same ratio 55 : 45 and using the same feeding management as in the early lactation experiment (Schei et al, 2007). Silage was stored in tower silos until start of the early lactation experiment, then packed in plastic bags and frozen until use also for the late lactation trial, to ensure that the same feed was used in both lactation stages.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations